Rancang Bangun Sistem Informasi Registrasi Dan Keanggotaan Komunitas Motor XMAN Kuningan Menggunakan PHP Dan MYSQL - Nunu Nugraha; Fikri Puji Nugraha (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2019)
The XMAN Kuningan community is a community of Yamaha NMAX motorcycle users in Kuningan Regency. The members of this community are Kuningan Regency people who own Yamaha XMAN Motorcycles. To be able to become a member of this community, prospective members must meet the predetermined requirements, that is, they are willing to obey the rules in this community, free from drugs and illegal drugs, and are willing to protect the good name of the community. Any community in Kuningan Regency who is a Yamaha NMAX motorbike driver can become a member of the Kuningan XMAN Motorcycle Community by registering themselves to the secretariat of the XMAN Kuningan Motorcycle Community. To register sometimes prospective members find it difficult to find the location of the XMAN Kuningan Motor Community secretariat. Likewise with prospective members who are far from the secretariat location will require time and money to come to the secretariat so that many Yamaha NMAX motorcycle owners are reluctant to come directly to the secretariat because they do not have enough time to come directly to the secretariat. a registration information system that is made web-based, using the programming language PHP and MySQL as its database and using the Waterfall system development method. This study aims to establish the process of recruiting members of the XMAN Kuningan Motor Community and facilitate the registration of registered members.Keywords: Waterfall, Management of registration registration, Web, PHP and MYSQL programming